Racism Dissemination Model and Simulation Analysis Considering Crowd Classification with Intervention Strategies - Dejen Ketema Mamo; Tarekegn Kassahun Mengstie (Complexity)
The extensive propagation of racism and the endless occurrence of racist speeches on social outlets imperil the harmony and resilience of societies. Consecutively, it is required to work in-depth analysis of the structure process, dynamical interaction, and intervention impact on racism spread and related devastation. As such, the diffusion of racism may flow via a socially contagious approach, in which racist ideologies bear like an infectious disease transmission. In this study, we propose and analyze the S1S2S3HRCI compartmental mathematical model to comprehend how racists disseminate their opinions and influence society with intervention strategies. We proved the well-posedness of the proposed model. Convection, hesitation, and rejection of racist ideology measure the strength of racist militancy. Through rigorous theoretical analysis, racism-free and racism-addicted equilibrium are locally and globally asymptotically stable if the effective threshold value Re<1 and Re>1, respectively. Sensitivity analyses are performed based on the effective threshold value to seek influential control parameters of the model. The result implies high levels of racist combativeness and low likelihood of rejection of awarded individuals have fostered racism dissemination. Nevertheless, effective antiracism education and racist confinement create a social environment beyond racism and reduce the peril of bigotry. Through extensive simulations, we study the racism dissemination process will decline and vanish if the community resilience boots via antiracism education and efficient racist confinement. Furthermore, racist confinement is more effective when compared to antiracism education. We examine the impact of integrating interventions, and the result exhibits that combining intervention strategies is better relevant than a sole intervention.